Communication Between Healthcare Providers and their Clients: How Accurately do Mothers Remember the Indications for the Caesarean Section that they had? - Enabudoso EJ; Ajakaiye LE; Okoror CEM (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: The indication for Caesarean delivery is one of the most important information required in the antenatal care and delivery mode for women with previous Caesarean section(s). Objective: To assess the level of agreement/disparity between mothers' report and the actual medical indication for Caesarean delivery and to explore factors associated with it. Methods: This cross-sectional study was carried out among 248 women who were delivered by Caesarean section. A comparison was done between the patient's report of the indication for the Caesarean section and the physician's record and the level of similarity was recorded. Results: More than half (126; 50.7%) of the respondents reported indications that were classified as complete similarity [Group A] while Groups B to E had 54 (21.8%), 21 (8.5%), 26 (10.5%) and 21 (8.5%) responses respectively. Of the group with "non-similar" responses, foetal indication accounted for 36.1% of them. Parity was the only predictor of "similarity". Compared to para 0, para 1-4 were more likely to report "similarity" in the indications for the Caesarean section (AOR = 3.370; 95% CI = 1.277-8.888). Conclusion: While the past obstetric history is an important aspect of the evaluation of the pregnant woman, it is important to attempt greater verification of facts at history taking for the indications for previous Caesarean section, especially when it has to do with foetal health as the indication, and in the nulliparae.